Variability as a Predictor for the Hard-to-soft State Transition in GX 339−4 - Matteo Lucchini; Marina Ten Have; Jingyi Wang; Jeroen Homan; Erin Kara; Oluwashina Adegoke; Riley Connors; Thomas Dauser; Javier Garcia; Guglielmo Mastroserio; Adam Ingram; Michiel van der Klis; et al. (The Astrophysical Journal, 2023)
During the outbursts of black hole X-ray binaries (BHXRBs), their accretion flows transition through several states. The source luminosity rises in the hard state, dominated by nonthermal emission, before transitioning to the blackbody-dominated soft state. As the luminosity decreases, the source transitions back into the hard state and fades to quiescence. This picture does not always hold, as ≈40% of the outbursts never leave the hard state. Identifying the physics that govern state transitions remains one of the outstanding open questions in black hole astrophysics. In this paper we present an analysis of archival RXTE data of multiple outbursts of GX 339−4. We compare the properties of the X-ray variability and time-averaged energy spectrum and demonstrate that the variability (quantified by the power spectral hue) systematically evolves ≈10–40 days ahead of the canonical state transition (quantified by a change in spectral hardness); no such evolution is found in hard-state-only outbursts. This indicates that the X-ray variability can be used to predict if and when the hard-to-soft state transition will occur. Finally, we find a similar behavior in 10 outbursts of four additional BHXRBs with more sparse observational coverage. Based on these findings, we suggest that state transitions in BHXRBs might be driven by a change in the turbulence in the outer regions of the disk, leading to a dramatic change in variability. This change is only seen in the spectrum days to weeks later, as the fluctuations propagate inwards toward the corona.